A systematic review assessing the potential use of cystatin c as a biomarker for kidney disease in people living with HIV on antiretroviral therapy - Hanser, Sidney; Choshi, Joel; Mokoena, Haskly; Mabhida, Sihle E.; Mchiza, Zandile J. R.; Moetlediwa, Marakiya T.; Muvhulawa, Ndivhuwo; Nkambule, Bongani B.; Ndwandwe, Duduzile; Nqebelele, Unati; Kengne, André P.; Dludla, Phiwayinkosi V. (Frontiers in Medicine, 2024)
Introduction of highly active antiretroviral therapy (HAARTART) has significantly prolonged the lives of people living with human immunodeficiency virus (PLWH). However, the continued use of this drug regimen has also been associated with a cluster of metabolic anomalies, including renal toxicity that can lead to the development of kidney diseases. Here, we reviewed studies that presented kidney disease in PLWH from electronic databases such as PubMed/MEDLINE, Scopus, and Google Scholar, and grey literature. The narrative synthesis of data from these clinical studies showed that the serum levels of cystatin C remained unchanged or were not affected in PLWH on HAARTART, while creatinine based glomerular filtration rate (GFR) fluctuated. In fact, some of the included studies showed that creatinine based GFR was increased in PLWH taking tenofovir disoproxil fumarate containing HAARTART. Perhaps indicating that the use of both cystatin C and creatinine based GFR is vital to monitor the development of kidney disease in PLWH. Clinical data summarized within this study indicates the potential detrimental effects of tenofovir based HAARTART regimen in causing renal tubular injury, while highlighting possible beneficial effects of dolutegravirbased HAARTART on improving kidney function in PLWH. However, summarized literature remains limited, while more clinical studies are required to inform on the potential use of cystatin C as a biomarker for kidney disease in PLWH.